Authenticity and Self‐Knowledge. (18th July 2013) - Feldman, Simon D.; Hazlett, Allan
Abstract: We argue that the value of authenticity does not explain the value of self‐knowledge. There are a plurality of species of authenticity; in this paper we consider four species: avoiding pretense (section 2), Frankfurtian wholeheartedness (section 3), existential self‐knowledge (section 4), and spontaneity (section 5). Our thesis is that, for each of these species, the value of (that species of) authenticity does not (partially) explain the value of self‐knowledge. Moreover, when it comes to spontaneity, the value of (that species of) authenticity conflicts with the value of self‐knowledge.